2018
DOI: 10.1021/acs.jmedchem.8b00002
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Novel 1,3-Oxazine Based β-Secretase (BACE1) Inhibitors: Incorporation of a Double Bond To Reduce P-gp Efflux Leading to Robust Aβ Reduction in the Brain

Abstract: Accumulation of Aβ peptides is a hallmark of Alzheimer's disease (AD) and is considered a causal factor in the pathogenesis of AD. β-Secretase (BACE1) is a key enzyme responsible for producing Aβ peptides, and thus agents that inhibit BACE1 should be beneficial for disease-modifying treatment of AD. Here we describe the discovery and optimization of novel oxazine-based BACE1 inhibitors by lowering amidine basicity with the incorporation of a double bond to improve brain penetration. Starting from a 1,3-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Sequence alignment analysis showed that the amino acid sequences of human BACE1 and BACE2 gene coding regions are 45% identical and 75% homologous [22]. Numerus crystal structures of BACE1 have been resolved with and without inhibitor in its active site [23][24][25][26][27][28][29][30][31][32]. BACE1 contains an N-terminal protease domain, a connecting strand, a transmembrane region, and a cytosolic domain [23].…”
Section: Function and Structure Of β-Secretasementioning
confidence: 99%
“…Sequence alignment analysis showed that the amino acid sequences of human BACE1 and BACE2 gene coding regions are 45% identical and 75% homologous [22]. Numerus crystal structures of BACE1 have been resolved with and without inhibitor in its active site [23][24][25][26][27][28][29][30][31][32]. BACE1 contains an N-terminal protease domain, a connecting strand, a transmembrane region, and a cytosolic domain [23].…”
Section: Function and Structure Of β-Secretasementioning
confidence: 99%
“…Considering our experience that lowering the p K a worked well in previous SAR efforts to address these issues, we adopted a similar strategy to optimize the dihydrothiazine series. With detailed knowledge of the optimal p K a range of the amidine moiety (6.5<p K a <7.4) to reduce hERG inhibition and P‐gp efflux as well as retaining cellular potency, our design efforts focused on incorporating electron withdrawing substituents into the dihydrothiazine head group. During this work, an elegant molecular design was disclosed by Hilpert et al.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical BACE1 assay . The biochemical BACE1 IC 50 values were determined by HTRF assay using an APP derived peptide as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations